KNITTING THE LIMITS OF FREEDOM: ARTICLE 1337 OF THE CIVIL LAW BOOK AND DYNAMICS OF BUSINESS CONTRACTS - Febrianty, Yenny; Putri, Viorizza Suciani; Riana, Ana; Syahbana, Rio Akmal; Fitriani, Rini; Yuliana, Tora (Paulus Law Journal, 2024)
This study's primary objective is to examine how Article 1337 of the Civil Code governs the boundaries of freedom of contract in Indonesian corporate contracts. This article aims to safeguard the parties' freedom to enter into agreements by preventing abuse that harms other parties or violates legal and moral standards. This research combines a normative technique with a legislative approach, closely examining primary, secondary, and tertiary legal texts to comprehend the application of Article 1337 in business practice. According to the findings, Article 1337 is crucial since it establishes explicit boundaries on contract freedom; yet, the efficacy of this provision is greatly reliant on the thoroughness of law enforcement and judicial interpretation. We identified subjectivity in determining public decency and order, along with an informational and power imbalance between the parties, as the primary obstacles to putting this article into practice. Therefore, consistent enforcement of the legislation and clearer standards are necessary for the fair and efficient enforcement of Article 1337.